The EU's "sanctions paradox" - Clara Portela (Stiftung Wissenschaft und Politik (SWP), 2007)
The forthcoming Summit meeting between the European Union (EU) and Africa next December will be the first event of this kind in the past seven years. However, the row over the participation of Zimbabwe's President, Robert Mugabe, is casting a shadow over the upcoming event: A number of African states have threatened to boycott the meeting if Zimbabwe's leader is not invited, while the British government has indi-cated that it will not attend the meeting if he does. At the root of this row is an 'EU sanction': a visa ban prohibiting the entry into EU territory to Zimbabwean high-rank officials. Zimbabwe has been under EU sanctions since the crisis of 2002. The visa ban and the arms embargo imposed then were supplemented shortly after by an assets freeze; however, no restrictions on trade between the EU and Zimbabwe have been imposed. European aid continues to flow to the country. So what do 'EU sanctions' consist of? What kind of measures are they, and why is it that they forbid the issue of visas to foreign leaders but leave trade untouched? What do we know about the harm they cause to their targets? Ought current EU practices be improved upon?
Keywords: 320